2004
DOI: 10.1021/jf021060m
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents in Baccharis dracunculifolia as the Main Botanical Origin of Southeastern Brazilian Propolis

Abstract: Previously, it was reported that one group of propolis (Group 12) was identified in southeastern Brazil, and the botanical origin of the propolis was Baccharis dracunculifolia resinous exudates. It was also observed that honeybee (Africanized Apis mellifera) mainly visited the leaf buds or unexpanded leaves of B. dracunculifolia but rarely expanded leaves. B. dracunculifolia is dioecious with male and female inflorescences, and RPHPLC of the ethanolic extracts of the respective male and female bud resinous exu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
161
2
58

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(236 citation statements)
references
References 12 publications
15
161
2
58
Order By: Relevance
“…Six microliters of the ethanolic extracts were applied, and an ascending chromatographic run with a mobile phase of ethanol:water (55:45 vol/vol) was performed during 1.5 hour. The detection of flavonoids was carried out by UV radiation at 366 nm (PARK et al, 2004). G12 propolis were also present in the ethanolic extracts of B. dracunculifolia leaf buds, although in different relative amounts (Table 1).…”
Section: Reversed-phase High-performance Thin Layer Chromatography (Rmentioning
confidence: 99%
“…Six microliters of the ethanolic extracts were applied, and an ascending chromatographic run with a mobile phase of ethanol:water (55:45 vol/vol) was performed during 1.5 hour. The detection of flavonoids was carried out by UV radiation at 366 nm (PARK et al, 2004). G12 propolis were also present in the ethanolic extracts of B. dracunculifolia leaf buds, although in different relative amounts (Table 1).…”
Section: Reversed-phase High-performance Thin Layer Chromatography (Rmentioning
confidence: 99%
“…Propolis has been used as folk medicine since ca. 300 BC, and it has also been reported that propolis has a wide range of biological activities including antioxidant, antimicrobial, anti-inflammatory, anti-tumoral, anti-HIV, and anti-dioxins (GHISALBERTI, 1979;BURDOCK, 1998;PARK et al, 2005). Recently, propolis has also been extensively used in foods and beverages as an ingredient of functional foods to improve health and prevent diseases (BURDOCK, 1998;PARK et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…300 BC, and it has also been reported that propolis has a wide range of biological activities including antioxidant, antimicrobial, anti-inflammatory, anti-tumoral, anti-HIV, and anti-dioxins (GHISALBERTI, 1979;BURDOCK, 1998;PARK et al, 2005). Recently, propolis has also been extensively used in foods and beverages as an ingredient of functional foods to improve health and prevent diseases (BURDOCK, 1998;PARK et al, 2004). These applications of propolis have led to increased interest in its chemical compositions because so far mainly polyphenol compounds have been identified in propolis collected by Apis mellifera, and the major polyphenols are flavonoid aglycones and their derivates (KONIG, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of the main flavonoids in propolis has been found to be quantitatively or qualitatively variable, depending on the environmental plant ecology (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, groups 1, 2, 6, and 7 are highly antagonistic to the growth of nasopharyngel carcinoma (KB), and groups 6 and 7 are also highly inhibitive against the growth of ileocecal adenocarcinoma (HCT-8), renal carcinoma CAKE-1, and breast carcinoma (MCT-7) tumor cell lines (17,18). The propolis group 12, which is known as green propolis, is widely used mainly for ingredients of functional foods and pharmaceutical purposes (15,16). The botanical origin of propolis group 12 was the resin of the leaf bud of Baccharis dracunculifolia in southeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%